Hubungan Lingkungan dan Sosial Budaya dengan Pengetahuan Orang Tua Terhadap Deteksi Dini Pendengaran Bayi Baru Lahir di Rumah Sakit Mitra Husada Pringsewu Lampung - Muslim Kasim; Upik Pebriani; Astri Pinilih; Amira Ainulwidad (Universitas Malahayati, 2021)
ABSTRACT:THE CORRELATION BETWEEN ENVIRONMENT AND SOCIO-CULTURAL WITH PARENT’S KNOWLEDGE TO EARLY DETECTION OF HEARING FOR NEWBORN BABY AT MITRA HUSADA HOSPITAL PRINGSEWU LAMPUNG Introduction: The incidence of deafness in newborns is 0.001% to 0.5% and increases in infants with risk factors reaching 1% -5%, which occurs in about 4-6 babies in 1000 live births in developing countries. Newborn hearing screening is a program to reduce the increasing incidence of hearing loss in the world. Knowing the child's hearing condition from an early age is an important thing to do where parental knowledge plays a role in early detection of hearing in infants. One of the factors that influence knowledge is environment and socio-culture. Purpose: To determine the environmental and socio-cultural relationship with parents' knowledge about early detection of hearing in newborns at Mitra Husada Pringsewu Hospital, Lampung. Method: The design of this study was an observational analytic with adesign cross sectional. The sample selection used total sampling of 60 respondents. Results: The data obtained were analyzed using thetest Chi-Square which showed that there was a significant relationship between the environment and parental knowledge where the p-value was 0.000 (p-value <0.005) with an OR of 13.00 and 95% CI 3.11-54.26 and the results of the analysis between social culture with parental knowledge showed significant results where the p-value was 0.015 with OR 4.42 and 95% CI 1.27-15.38. Conclusion: There is a significant relationship between environment and socio-culture with parents' knowledge of early detection of hearing of newborns at Mitra Husada Pringsewu Hospital, Lampung. Keywords : Parent’s knowledge, Early Hearing Detection, Environment, Socio-cultural INTISARI : Hubungan Lingkungan Dan Sosial Budaya Dengan Pengetahuan Orang Tua Terhadap Deteksi Dini Pendengaran Bayi Baru Lahir Di Rumah Sakit Mitra Husada Pringsewu Lampung Latar Belakang: Insidensi ketulian pada bayi baru lahir 0,001-0,5% dan meningkat pada bayi dengan faktor risiko mencapai 1%-5%, dimana terjadi pada sekitar 4-6 bayi pada 1000 kelahiran hidup. Skrining pendengaran bayi baru lahir merupakan program untuk mengurangi angka kejadian gangguan pendengaran di dunia yang semakin meningkat. Mengetahui kondisi pendengaran anak sejak dini merupakan hal yang penting, dimana pengetahuan orang tua berperan terhadap deteksi dini pendengaran pada bayi. Salah satu faktor yang mempengaruhi pengetahuan adalah lingkungan dan sosial budaya. Tujuan: Mengetahui hubungan lingkungan dan sosial budaya dengan pengetahuan orang tua tentang deteksi dini pendengaran pada bayi baru lahir di Rumah Sakit Mitra Husada Pringsewu Lampung. Metode Penelitian: Desain penelitian ini adalah analitik observational dengan rancangan Cross Sectional. menggunakan Total Sampling sebanyak 60 responden. Hasil: Data yang diperoleh dianalisis dengan uji Chi-Square menunjukan terdapat hubungan yang signifikan antara lingkungan dengan pengetahuan orang tua dimana p-value 0.000 (< 0,005) dengan OR 13.00 dan CI 95% 3.11-54.26 dan hasil analisis antara sosial budaya dengan pengetahuan orangtua menunjukkan hasil yang signifikan dimana p-value 0.015 dengan OR 4.42 dan CI 95% 1.27-15.38. Kesimpulan: Terdapat hubungan yang signifikan antara lingkungan dan sosial budaya dengan pengetahuan orang tua terhadap deteksi dini pendengaran bayi baru lahir di Rumah Sakit Mitra Husada Pringsewu Lampung. Kata Kunci: Pengetahuan Orang Tua, Deteksi Dini Pendengaran, Lingkungan, Sosial Budaya